2020
DOI: 10.3389/fmicb.2019.03058
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by Metal Ions in Bioleaching of LiCoO2 by an Acidophilic Microbial Consortium

Abstract: An acidophilic microbial consortium (AMC) was used to investigate the fundamental mechanism behind the adverse effects of pulp density increase in the bioleaching of waste lithium ion batteries (WLIBs). Results showed that there existed the effect of metal-ion stress on the bio-oxidative activity of AMC. The Li + and Co 2+ accumulated in the leachate were the direct cause for the decrease in lithium and cobalt recovery yields under a high pulp density. In a simulated bioleaching system with 4.0% (w •v −1) LiCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…This is consistent with previous studies that suggested proteobacteria have the strongest ROS defense signature across domain bacteria [23,99]. It has also been suggested that during high ROS stress in bacteria, the hydrogen peroxide-inducible genes activator protein regulator (OxyR) is activated and an increased expression and activity of the oxidative stress responses of AhpC and catalase are observed [23,107]. Genes encoding OxyR were identified in all of the Acidihalobacter species.…”
Section: Catalase and Alkyl Hydroperoxide Reductasesupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with previous studies that suggested proteobacteria have the strongest ROS defense signature across domain bacteria [23,99]. It has also been suggested that during high ROS stress in bacteria, the hydrogen peroxide-inducible genes activator protein regulator (OxyR) is activated and an increased expression and activity of the oxidative stress responses of AhpC and catalase are observed [23,107]. Genes encoding OxyR were identified in all of the Acidihalobacter species.…”
Section: Catalase and Alkyl Hydroperoxide Reductasesupporting
confidence: 91%
“…It has been shown that the mutual regulation and expression of catalase and ahpC genes results in dual response to oxidative stress [106]. This is consistent with previous studies that suggested proteobacteria have the strongest ROS defense signature across domain bacteria [23,99]. It has also been suggested that during high ROS stress in bacteria, the hydrogen peroxide-inducible genes activator protein regulator (OxyR) is activated and an increased expression and activity of the oxidative stress responses of AhpC and catalase are observed [23,107].…”
Section: Catalase and Alkyl Hydroperoxide Reductasesupporting
confidence: 89%
See 1 more Smart Citation
“…The synergistic effect of Li + and Co 2+ , accumulated in the leachate in the simulated bioleaching system with 4.0% of LiCoO 2 slurry, has been shown to cause the oxidative stress in the acidophilic microbial consortium including mainly Sb. thermosulfidooxidans and L. ferriphilum [ 75 ]. Although the oxidative stress results in increased intracellular ROS, the addition of the exogenous glutathione (which acts as an antioxidant) increases the activities of GSH peroxidase and catalase to scavenge the excessive intracellular ROS, and this results in improved bioleaching of LiCO 2 by the community [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…thermosulfidooxidans and L. ferriphilum [ 75 ]. Although the oxidative stress results in increased intracellular ROS, the addition of the exogenous glutathione (which acts as an antioxidant) increases the activities of GSH peroxidase and catalase to scavenge the excessive intracellular ROS, and this results in improved bioleaching of LiCO 2 by the community [ 75 ].…”
Section: Resultsmentioning
confidence: 99%